Double Wenckebach phenomenon in atrioventricular node and His bundle. Electrophysiological demonstration in a case of atrial flutter. Issue 3 (March 1981) - Slama, R; Sebag, C; Motte, G; Leclercq, J F
Abstract : In a case of atrial flutter with a 9:2 atrioventricular response, the only possible way to explain the conduction pattern was 3:1 block in the atrioventicular node (which is 3:2 Wenckebach sequence in the N zone and a 2:1 block at the junction of the node with the bundle of His) plus 3:2 Wenckebach sequence distal to the H deflection. The recording of the His bundle deflection confirmed this analysis.